High temperature performance of cement mortars with incorporation of PEG-based form-stable Phase Change Materials - Cunha, Sandra Raquel Leite (2024)
The integration of a phase change material in mortar promises to improve thermal comfort and reduce energy consumption. Assessing mortar behavior under diverse temperature conditions, especially high ones encountered in unforeseen disasters or accidents, is essential for evaluating their reliability and resilience in safeguarding building safety and longevity. This research examines the behavior of cement-based mortar, containing a sustainable PCM incorporated into porous aggregates from processing waste, when exposed to different temperatures (i.e., 20, 200, 600 ◦C). A comprehensive study on the physical properties of the cement-based mortar formulations (with and without the phase change materials) has been conducted, revealing an increase in the flexural and compressive strengths for a temperature exposure of 200ºC, due to the acceleration of the hydration process of the binder. However, a decrease in flexural and compressive strengths, as well as adhesion, for the temperature exposure of 600ºC was observed, due to the microcracks developed due the high thermal gradient. This behavior is observable even in mortars that do not contain any phase change material. Thermal cycle test of the phase change material involved in this work (i.e., Polyethylene-glycol of molecular weight 1000) has been carried out: stable melting and crystallization temperatures were recorded with a maximum enthalpy variation of 5 %.